2020
DOI: 10.3389/fmed.2020.00062
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Autonomic Nervous System and Neurotrophic Factors Regulate the Pathogenesis and Progression of Non-alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease represents a continuum of excessive hepatic steatosis, inflammation and fibrosis. It is a growing epidemic in the United States of America and worldwide. Progression of non-alcoholic fatty liver disease can lead to morbidity and mortality due to complications such as cirrhosis or hepatocellular carcinoma. Pathogenesis of non-alcoholic fatty liver disease is centered on increased hepatic lipogenesis and decreased hepatic lipolysis in the setting of hepatic and systemic insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 97 publications
2
25
0
Order By: Relevance
“…ANS-mediated hepatic functions include regulation of glucose and lipid metabolism, nutrient sensing, ion sensing and osmotic pressure, drug metabolism (CYP enzymes), blood flow, the biliary system, circadian rhythm, and hepatic regeneration and repair. Furthermore, the ANS has been implicated in the pathogenesis and progression of NAFLD [ 7 ]. Autonomic dysfunction is a hallmark of psychiatric as well as metabolic disease [ 68 , 69 , 70 , 71 ], and some side effects associated with AA therapy are consistent with medication-associated increase in sympathetic tone [ 50 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANS-mediated hepatic functions include regulation of glucose and lipid metabolism, nutrient sensing, ion sensing and osmotic pressure, drug metabolism (CYP enzymes), blood flow, the biliary system, circadian rhythm, and hepatic regeneration and repair. Furthermore, the ANS has been implicated in the pathogenesis and progression of NAFLD [ 7 ]. Autonomic dysfunction is a hallmark of psychiatric as well as metabolic disease [ 68 , 69 , 70 , 71 ], and some side effects associated with AA therapy are consistent with medication-associated increase in sympathetic tone [ 50 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe mental illness, including schizophrenia, experience a significantly shortened life expectancy with high rates of all-cause mortality [ 1 , 2 , 3 ], most commonly associated with metabolic dysregulation and cardiovascular disease. Non-alcoholic fatty liver disease (NAFLD) is a growing epidemic worldwide and is associated with obesity, insulin resistance, and inflammation [ 4 , 5 , 6 , 7 ]. Incidence of NAFLD is elevated in patients with severe mental illness [ 3 ] and with atypical antipsychotic (AA) treatment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying the association between HRV and NAFLD are not yet fully understood, but there is growing evidence to suggest that autonomic dysfunction affects the risk of NAFLD and disease progression. Preclinical studies have demonstrated that an increase in SNS activity and adrenergic signaling causes HS and NASH-cirrhosis, while an increase in PNS activity inhibits the process from HS to NASH-cirrhosis 16 . Moreover, selective hepatic sympathetic denervation in mice led to almost complete resolution of HS in 1 week 28 , while hepatic vagotomy was found to exacerbate HS and hepatic inflammation in a mouse model 16 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The liver is innervated by both the sympathetic and parasympathetic nervous systems, both of which play an important role in the autonomic regulation of glucose and lipid metabolism 14 , 15 . Interestingly, several experimental studies have demonstrated that increased sympathetic nervous activity could induce NAFLD and influence its progression, even non-alcoholic steatohepatitis (NASH)-cirrhosis, whereas parasympathetic activation reduces progression 16 , suggesting its potential role in the autonomic imbalance in the pathogenesis of NAFLD. To date, no cohort studies have addressed whether low HRV, reflective of autonomic imbalance, is associated with the risk and progression of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…The liver receives innervation from the autonomic nervous system, including the sympathetic and parasympathetic nervous systems (Furness et al, 2014). Sympathetic nerves, as regulators, are involved in hepatic lipid metabolism (Amir et al, 2020). Sympathetic hyperactivation promoted hepatic steatosis.…”
Section: Introductionmentioning
confidence: 99%